Achieving Highly Efficient Pure Organic Single‐Molecule White‐Light Emitter: The Coenhanced Fluorescence and Phosphorescence Dual Emission by Tailoring Alkoxy Substituents. Issue 7 (5th February 2020) - Wen, Yating; Liu, Haichao; Zhang, Shitong; Cao, Jungang; De, Jianbo; Yang, Bing
Abstract: Developing the single‐molecule white‐light emitters (SMWLEs) at room temperature is very challenging for pure organic metal‐free system, and it is even more challenging to achieve the high efficiency of pure organic SMWLE. Here, alkoxy substituents are tailored at 2‐positioned thioxanthone (TX) to finely tune the molecular packing mode and the intermolecular interaction between TX units, and the photoluminescence (PL) efficiency (ΦPL ) of SMWLE is improved successfully from 1.5% (TX) to 45.0% (TX‐OCH(CH3 )2 ). This simultaneous enhancement of dual emission between fluorescence and phosphorescence can be ascribed to i) a moderate intersystem crossing (ISC) rate for the equilibrium distribution between singlet and triplet excitons, ii) simultaneously accelerated radiative rates of singlet and triplet excitons due to J‐aggregation of TX units, and iii) effective suppression of nonradiation through strong hydrogen bond interactions by alkoxy chains. As a result, this work provides a novel molecular design strategy to harvest high‐efficiency pure organic SMWLE using a precise manipulation of π–π stacking mode and intermolecular interaction by tailoring alkoxy substituents. Abstract : High‐efficiency pure organic single‐molecule white‐light emitter can be achieved by tailoring alkoxy side chains at 2‐positioned thioxanthone (TX) to finely tune the molecular packing and the intermolecular interaction. The novel strategy successfully improves the photoluminescence (PL) efficiency (ΦPL ) from 1.5% (TX) to 45.0% (TX‐OCH(CH3 )2 ).